Investigation of iron hexacyanoferrate as a high rate cathode for aqueous batteries: Sodium-ion batteries and lithium-ion batteries. (20th April 2018) - Yang, Qin; Wang, Wei; Li, Hai; Zhang, Juan; Kang, Feiyu; Li, Baohua
Abstract: In this study, highly crystalline FeFe(CN)6 with metal-organic framework is synthesized and measured in NaNO3 and LiNO3 . Electrochemical kinetics, physical and chemical changes about the insertion and extraction processes of sodium ions and lithium ions in FeFe(CN)6 are compared and discussed. Intriguingly, it exhibits a good electrochemical performance in sodium aqueous batteries, with a capacity of 118 mAh g −1 at 400 mA g −1, but a poor electrochemical behavior in lithium aqueous batteries. This study sheds light on the different insertion processes between sodium ions and lithium ions in FeFe(CN)6, that the outer petaloid-like structure forms on the surface of FeFe(CN)6 after Li ions insertion with little volume expansion, while FeFe(CN)6 after Na ions insertion could still maintain the cubic-like structure with lattice change. Different insertion mechanisms of sodium ions and lithium ions are proposed that hydrated Na ions could insert at interstitial sites, while hydrated Li ions are more likely to occupy large open sites due to the larger radius of hydrated Li ions than hydrated Na ions. Besides, insertion/extraction performance and capacitive preformance dominate in NaNO3 and LiNO3, respectively. These differences may lead to the different electrochemical behaviors between sodium-ion and lithium-ion aqueous batteries. Graphical abstract: Hydrated Na ions could insert at interstitial sites, while hydrated Li ions are more likely to occupy large open sites. This difference could lead to the better electrochemical behavior of FeFe(CN)6 in storing sodium ions than storing lithium ions for aqueous batteries. Highlights: Highly crystalline of FeFe(CN)6 is synthesized with lattice parameter of 10.18 Å. The electrochemical behavior of FeFe(CN)6 in NaNO3 is more stable than in LiNO3 . FeFe(CN)6 exhibits high capacity of 118 mAh g −1 at 400 mA g −1 in NaNO3 . Hydrated Li ions are more likely to occupy open sites rather than interstitial sites. The poor electrochemical performance of FeFe(CN)6 in LiNO3 may be attributed to occupation at open sites.